2007
DOI: 10.4319/lo.2007.52.1.0060
|View full text |Cite
|
Sign up to set email alerts
|

Effects of upstream lakes on dissolved organic matter in streams

Abstract: We examined the effects of upstream lakes on dissolved organic matter (DOM) quantity and the absorbance of ultraviolet (UV) radiation in the streams of northern Michigan. We assessed DOM concentration and absorbance in 15 streams with upstream lakes and 17 streams without upstream lakes located in the same geographic region in May and August 2003. In addition, we estimated watershed land cover and morphology to assess the possibility that other landscape variables could account for DOM differences between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 41 publications
2
67
2
Order By: Relevance
“…The interaction of these factors and their capacity to alter the transport and processing of carbon and nutrients makes it challenging to predict patterns based on classic models of river function (e.g., River Continuum Concept [Vannote et al, 1980]) or based on previous research in large rivers without impoundments or free flowing headwaters. For example, in riverine systems with lentic headwaters and/or significant impoundments the potential for decoupling between CDOM production and DOC accumulation may result in weaker relationships between CDOM absorbance and DOC [Larson et al, 2007;Miller, 2012;Spencer et al, 2012]. However, our study observed a strong relationship between CDOM absorbance values and DOC, suggesting that lentic headwaters and significant impoundment may not be a universal impediment to deriving relationships between CDOM absorbance and DOC or that the Klamath is more dominated by allochthonous CDOM inputs than previously studied impounded systems.…”
Section: Discussioncontrasting
confidence: 51%
“…The interaction of these factors and their capacity to alter the transport and processing of carbon and nutrients makes it challenging to predict patterns based on classic models of river function (e.g., River Continuum Concept [Vannote et al, 1980]) or based on previous research in large rivers without impoundments or free flowing headwaters. For example, in riverine systems with lentic headwaters and/or significant impoundments the potential for decoupling between CDOM production and DOC accumulation may result in weaker relationships between CDOM absorbance and DOC [Larson et al, 2007;Miller, 2012;Spencer et al, 2012]. However, our study observed a strong relationship between CDOM absorbance values and DOC, suggesting that lentic headwaters and significant impoundment may not be a universal impediment to deriving relationships between CDOM absorbance and DOC or that the Klamath is more dominated by allochthonous CDOM inputs than previously studied impounded systems.…”
Section: Discussioncontrasting
confidence: 51%
“…These findings indicate that regional hydrogeologic and climatic conditions play an important role in driving DOC variability (Sobek et al, 2007;Duarte et al, 2008;Jaffé et al, 2008). In the brackish waters, DOC accumulates via runoff passing through various landscapes (Larson et al, 2007;C. C. Song et al, 2011), and can be lost from these brackish waters through sinking to the bottom Tranvik et al, 2009;Barros et al, 2011) or being transformed into DIC (includes CO 2 ) in the water column (Brooks and Lemon, 2007;Duarte et al, 2008;Tranvik et al, 2009).…”
Section: Dissolved Organic Carbon In Fresh and Brackish Watersmentioning
confidence: 99%
“…DOC mass balances are subject to the influences of temperature and precipitation, which can have important effects on DOC source, transport and fate (Larson et al, 2007;Jaffé et al, 2008;Fellman et al, 2011). Studies have indicated that concentrations of DOC in inland waters tend to decrease with increasing water residence times due to increased photobleaching and microbial activities (Curtis and Adams, 1995;Helms et al, 2008;Julian et al, 2008Julian et al, , 2011Stedmon et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…[29] The magnitude of allochthonous OM inputs into a water body is often related to the size of the drainage area [e.g., Carignan and Steedman, 2000;Larson et al, 2007], with higher DOC concentrations measured for aquatic system with high watershed area to lake area ratio. In this study, significant correlations between DOC concentrations and this ratio were obtained only when the natural lakes were plotted with the wood harvested systems (Lake Bouleau excluded), suggesting that DOC concentrations are more closely linked to the additional inputs of allochthonous OM caused by increased erosion and OM leaching in the wood harvested systems rather than to natural OM inputs from a large watershed [Sobek et al, 2003].…”
Section: Using Water Chemistry and Bulk Analyses To Study Carbon Cyclmentioning
confidence: 99%